Oxygen Transport to Tissue XXXI - Takahashi, Eiji.; Bruley, Duane F.; SpringerLink (Online service) (Boston, MA : Springer US, 2010)
This book covers all aspects involved in uptake of oxygen from the air, transport by blood stream, and its ultimate consumption in the cell in various organs as discussed at the 36th Annual Meeting of the International Society on Oxygen Transport to Tissue (ISOTT) held in Sapporo, Japan in August 2008. Special attention will be paid to methods of oxygen measurement in living tissue and application of these technologies to understanding physiological and biochemical basis for pathology related to tissue oxygenation. This book is multidisciplinary and designed to bring together experts and students from a range of research fields including biomedical engineering, physiology, biochemistry, molecular biology, and clinical medicine.
Keywords: Medicine; Human physiology; Immunology; Pneumology; Biomedicine; Human Physiology; Immunology; Pneumology/Respiratory System